Leitura e gêneros textuais em livros didáticos de língua inglesa do Ensino Médio - ARAÚJO, Marcus de Souza (2006)
This study is aimed at analyzing the question of written comprehension activities from the perspective of the approach of genre on English textbooks on High School level. Therefore, it intends to discuss the ways in which reading activities work genre in a communicative way. For this, we examine genres, the types of activities and types of written comprehension questions present in two textbooks. Futhermore, it is focused on investigating to what extent the reading strategies have been worked, explicit or implicitly, as a tool that facilitates the construction of meanings from the texts. The research methodology underlying this study was based on a focused description (Larsen-Freeman & Long, 1991) that selected two textbooks in a single volume. These English books were published in 2004 and used in private schools in Belem. This research was based on the theoretical framework of genre (Bakhtin [1952-53] 2003; Swales, 1990, 1992 and 1998; Marcuschi, 2002, 2003, 2004 and 2005; Ramos, 2004 and others); on the teaching of English reading (Dias, 2002 , 2005; Grabe & Stoller, 2001, 2002; Koda, 2005 among others) and on the use of the English textbooks (Day & Park, 2005; Garinger, 2001; Souza, 1999 and others). In addition, this study has its basis on the National Curriculum Parameters for the teaching of reading in a foreign language on High School level (PCNEM-LE, 2000, 2002, 2004). It is also verified that textbooks do not favor the activities in a communicative way for the construction of meaning in written comprehension, and besides the textbooks do not take genres as teaching tools. This construction is conjured by translation (or copy) of information of the text. The data analysis results still show the implicit use of reading strategies, without an awareness that favors the search of more critical and significant ways to help student?s learning. These results have pedagogical implications especially because it urges the opening for new spaces in the Brazilian educational scenario. This way, the use of these textbooks can be redefined and reflected in the teaching and learning of English as a foreign language.